The development of tourism destinations based on natural tourism potential in Lohia District, Muna Regency - Sainu, Muhammad Afal; Hermawan, Rachmad; Kosmaryandi, Nandi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Natural tourism objects and attractions (NTOA) can be developed as tourist destinations to improve the regional economy and community welfare. Therefore, it is necessary to determine the priority of NTOA development. This study aimed to determine the classification of NTOA development potential and formulate the development directions of natural tourism destinations in Lohia District, Muna Regency. Analysis of NTOA development potential based on modifications to the Guidelines for Operational Area Analysis - Objects and Natural Tourism Attractions (OAAONTA) and formulation of development directions was using SWOT analysis. The results showed that the classification of NTOA Meleura Beach, Napabale Lake, and Motonuno Lake was classified as very potential, while the NTOA Wakila Peak and Liangkabori Cave were classified as potential. The direction of NTOA development in Lohia District, namely: (1) development according to NTOA potential; (2) improving the information media and tourism promotion; (3) preparation of the NTOA management plan; (4) inviting investors for NTOA development; (5) monitoring and evaluation of tourism impacts; (6) involving the community as a driver of tourism activities.